2016
DOI: 10.6061/clinics/2016(12)10
|View full text |Cite
|
Sign up to set email alerts
|

Detection value of free cancer cells in peritoneal washing in gastric cancer: a systematic review and meta-analysis

Abstract: Intraperitoneal free cancer cells in gastric adenocarcinoma are associated with a poor outcome. However, the true prognostic value of intraperitoneal free cancer cells is still unclear, leading to a lack of consensus in the management of gastric cancer. The aim of the present study is to perform a systematic review and meta-analysis to analyze intraperitoneal free cancer cells-positive patients with regard to tumor oncologic stage, recurrence, grade of cellular differentiation, and survival rates and to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 92 publications
0
11
0
1
Order By: Relevance
“…The exact prognostication of advanced gastric cancer patients with positive peritoneal washing cytology result is difficult due to variability in enrolled patients, peritoneal washing methods, and treatment of cancer patients in these studies. Recent systemic reviews and meta-analyses have shown that peritoneal washing cytology is useful for determining the prognosis of advanced gastric cancer patients [265266267268].…”
Section: Pathologymentioning
confidence: 99%
“…The exact prognostication of advanced gastric cancer patients with positive peritoneal washing cytology result is difficult due to variability in enrolled patients, peritoneal washing methods, and treatment of cancer patients in these studies. Recent systemic reviews and meta-analyses have shown that peritoneal washing cytology is useful for determining the prognosis of advanced gastric cancer patients [265266267268].…”
Section: Pathologymentioning
confidence: 99%
“…Conventional peritoneal washing has low sensitivity and immunohistochemical and molecular techniques may be used to increase detection. Negativity cytology must be interpreted according to patient`s disease context and the surgeon`s impression 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative detection of free cancer cells in peritoneal lavage fluid by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) for carcinoembryonic antigen (CEA) has been reported to be a reliable method for predicting metachronous peritoneal carcinomatosis and cancer-related mortality after curative resection in gastric cancer patients. [10][11][12][13][14] This method may also allow for sensitive detection of residual cancer cells in CRC patients. 15 In light of the relatively low incidence of peritoneal recurrence and high incidence of locoregional recurrence in patients with CRC, detecting free cancer cells with a highly sensitive method can be a better predictor for patients who underwent curative resection.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of PCR‐based methods for detecting intraperitoneal free cancer cells has been demonstrated in patients with gastric cancer, mainly in terms of predicting peritoneal recurrence. Quantitative detection of free cancer cells in peritoneal lavage fluid by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) for carcinoembryonic antigen (CEA) has been reported to be a reliable method for predicting metachronous peritoneal carcinomatosis and cancer‐related mortality after curative resection in gastric cancer patients 10–14 . This method may also allow for sensitive detection of residual cancer cells in CRC patients 15 .…”
Section: Introductionmentioning
confidence: 99%